PENGEMBANGAN MEDIA PEMBELAJARAN POP- UP BOOK PANCA INDRA (POPANDRA) TERHADAP PEMAHAMAN SISWA PADA MATERI PANCA INDRA KELAS 1 DI SD NEGERI 2 SELODOKO - Widia Kristianingrum; Elvira Hoesein Radia (PIONIR: JURNAL PENDIDIKAN, 2022)
The lack of use of learning media in schools and teacher-centered learning using the lecture method has an impact on low student learning outcomes. This study aims to develop a pop-up book learning media for students' understanding of the five senses material for grade 1 elementary school students. This development research uses the ADDIE research method. The sample taken from this study was a grade 1 student at SD Negeri 2 Selodoko. The final result of this study is a pop-up book learning medium for grade 1 on the material of the five human senses. Based on the results of the study, it shows that (1) pop-up book learning media developed using the ADDIE method go through 5 stages, namely analysis, planning, development, implementation and evaluation. (2) based on the results of the pop-up book learning media validators, it was declared valid with an assessment from media experts of 73%, material experts of 87.5% and Linguists of 63%. (3) based on the results of the pre-test and post-test students also showed an increase from an average of 71 to 91, it shows that pop-up book learning media is effectively used in the material of the five senses of grade 1 at SD Negeri 2 Selodoko.